The Issue of Native and Non-Native English-Speaking Teachers: Which is the Ideal English Teacher? - Fitria, Tira Nur (English Language Education, Universitas Internasional Batam, 2023)
This research investigates the perceptions of Indonesian students regarding the ideals of native English-speaking teachers (NESTs) and non-native English-speaking teachers (NNESTs) in English Language Teaching (ELT). This research is library research that reviews recent research on native English teachers and non-native English teachers related to the implications of the research in ELT. The analysis shows that NESTs and NNESTs demonstrate significant distinctions in their teaching. These distinctions can be influenced by their strengths and weaknesses. It cannot be denied that the differences may influence students’ perceptions/opinions of the ideal English teachers. Several previous studies state the students’ positive perceptions between NESTs and NNESTs in teaching. The research tries to combine the perceptions of the two. Both NESTs and NNESTs should ideally have identical opportunities to become ideal English teachers within the context of English as a Foreign Language (EFL). Both NESTs and NNESTs have an equal opportunity to be ideal teachers and play the main functions in the educational context in Indonesia. However, they should have a strong command of the language, strong teaching skills, and positive personal qualities. Teaching English must emphasize the content of the teacher's skills rather than the irrelevant non-native status. It is expected that the issue of nativeness does not affect student perceptions of NESTs and NNESTs in terms of ideal for English teachers later. For the continued development of EFL in Indonesia, the availability of qualified English teachers is crucial. They must possess at least three essential skills including linguistic, pedagogical, and cultural.